PENGARUH LAMA PEMBERIAN BUNGKIL INTI SAWIT (BIS) DALAM RANSUM TERHADAP KOMPOSISI KIMIA DAN KOLESTROL DAGING BABI LANDRACE - Tjokorda Istri Putri (Udayana University, 2019)
Utilization of palm kernel meal in the diet was evaluated on the chemical composition and cholesterol content of pig. Twelve of 36 weeks old landrace barrow, average weight gain 93-97 kg was used in this experiment. Two diets RI without palm kernel meal and R II with 22% palm kernel meal were applied to the animals. Energy, crude protein content of R I and R II were 3313 kcal DE/kg and 12.32% CP and 3329 kcal DE/kg and 13.26 % CP respectively. The experiment was carried out in a completely randomized design with four treatments were R I6 (the animals were fed RI for 6 weeks period), R I4 R II2 (the animals were fed R I for 4 weeks and R II for the last 2 weeks), R I2 R II4 the animals were fed R I for the first 2 weeks and R II for the last 4 weeks) and R II6 (the animals were fed RII for 6 weeks period). Each treatment was replicated three times with one pigs for each replicated. The result of this experiment showed that cholesterol content on ham, chemical composition (water, crude protein and ether extract) of loin and ham were not signification, loin cholesterol content on RI4, RII2, RI2 RII4 and RII6 was 24.40 ; 13.50, and 28.80% respectively and less than RI6. Key word: palm kernel meal, chemical composition, cholesterol content